KEADAAN SOSIAL EKONOMI NELAYAN TRADISIONAL ALAT TANGKAP JUBI DI DESA JAYAKARSA KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA - Mailangkay, Immanuel J.; Longdong, Florence V.; Wasak, Martha P.; Manoppo, Victoria E.N.; Aling, Djuwita R.R. (AKULTURASI, 2022)
Abstract Jayakarsa Village is one of the villages located in West Likupang District, North Minahasa Regency, North Sulawesi Province, the local population is fishermen. Arrow or Jubi in terms of many areas in North Sulawesi is a fishing technique that still survives to this day. Capture fisheries which are still classified as traditional are still being carried out because in addition to hereditary efforts, this business also provides benefits for traditional fishing communities. is knowing the socio-economic conditions of traditional fishermen and analyzed based on descriptive quantitative and qualitative descriptive analysis. The data collected consists of primary data and secondary data. Primary data was collected through interviews guided by a questionnaire. Secondary data is data obtained from other sources as additional information, through books, journals, government publications, as well as websites or other supporting sources. The results showed that the socio-economic conditions of traditional jubi fishing gear in Jayakarsa Village were based on social aspects, namely the education level of the majority of fishermen respondents was junior high school (15%). Family dependents 3 people (55%) respondents. work experience ranges from 5 to 60 years. The majority of respondents are in the productive age, namely 15-64 years (90%). The social organization that fishermen participate in is mapalus. The health of the majority of fishermen experience ear problems, namely hearing, with the presence of covid 19 fishermen follow government directions by following health protocols and vaccinations. Fishermen usually watch television with their families on holidays or do not go to sea, the majority of fishermen do not have television or radio. The economic aspect of the respondent's investment capital needed for fishing business using jubi fishing gear in Jayakarsa Village requires a capital of Rp. 2,825,000. The income of respondents with jubi fishing gear has the majority income of Rp. 32,000,000 (50%). The respondent's expenditure has the majority of Rp. 9,000,000 (50%). Keywords: fisherman; spear gun; Jayakarsa Village; socio-economic Abstrak Desa Jayakarsa merupakan salah satu desa yang berada di Kecamatan Likupang Barat, Kabupaten Minahasa Utara, Provinsi Sulawesi Utara, penduduk setempat bermata pencaharian nelayan. Panah atau Jubi dalam istilah pada banyak daerah di Sulawesi Utara merupakan teknik penangkapan ikan yang masih bertahan sampai saat ini perikanan tangkap yang masih tergolong tradisional yang ada masih dilakukan karena selain usaha turun temurun, usaha ini juga memberikan keuntungan bagi masyarakat nelayan tradisional Tujuan dari penelitian ini adalah mengetahui keadaan sosial ekonomi nelayan tradisional dan dianalisis berdasarkan analisis deskriptif kuantitatif dan deskriptif kualitatif. Data yang dikumpulkan terdiri atas data primer dan data sekunder. Pengumpulan data primer dilakukan melalui wawancara yang dipandu dengan kuesioner. Data sekunder adalah data yang didapat dari sumber yang lain sebagai tambahan informasi, melalui buku, jurnal, publikasi pemerintah, serta situs atau sumber lain yang mendukung. Hasil penelitian menunjukkan bahwa keadaan sosial ekonomi nelayan tradisonal alat tangkap jubi di Desa Jayakarsa berdasarkan aspek sosial yaitu tingkat pendidikan mayoritas responden nelayan adalah SMP sebanyak (15%). Tanggungan keluarga 3 orang (55%) reponden. pengalaman kerja berkisar 5 sampai 60 tahun.Umur responden mayoritas berada pada usia produktif yaitu 15-64 tahun (90%). Organisasi sosial yang di ikuti nelayan adalah mapalus. Kesehatan mayoritas nelayan mengalami gangguan pada telinga yaitu pendengaran, dengan adanya covid 19 nelayan mengikuti arahan pemerintah dengan mengikuti protokol kesehatan dan vaksinansi.Nelayan biasanya menonton televisi bersama keluarga pada saat hari libur atau tidak melaut mayoritas nelayan tidak mempunyai televise maupun radio. Aspek ekonomi modal investasi responden yang dibutuhkan untuk usaha penangkapan ikan menggunakan alat tangkap jubi di di Desa Jayakarsa dibutuhkan modal sebesar Rp.2.825.000. Pendapatan responden alat tangkap jubi mempunyai pendapatan mayoritas sebesar Rp.32.000.000 (50%). Pengeluaran responden mempunyai pengeluaran mayoritas sebesar Rp9.000.000 (50%). Kata Kunci: nelayan; alat tangkap jubi; Desa Jayakarsa; sosial ekonomi